First-Trimester Crown-Rump Length and Embryonic Volume of Fetuses with Structural Congenital Abnormalities Measured in Virtual Reality: An Observational Study. (21st March 2017) - Baken, L.; Benoit, B.; Koning, A. H. J.; van der Spek, P. J.; Steegers, E. A. P.; Exalto, N.
Abstract : Background. With the introduction of three-dimensional (3D) ultrasound it has become possible to measure volumes. The relative increase in embryonic volume (EV) is much larger than that of the crown-rump length (CRL) over the same time period. We examined whether EV is a better parameter to determine growth restriction in fetuses with structural congenital abnormalities. Study Design, Subjects, and Outcome Measures. CRL and EV were measured using a Virtual Reality (VR) system in prospectively collected 3D ultrasound volumes of 56 fetuses diagnosed with structural congenital abnormalities in the first trimester of pregnancy (gestational age 7 +5 to 14 +5 weeks). Measured CRL and EV were converted to z -scores and to percentages of the expected mean using previously published reference curves of euploid fetuses. The one-sample t -test was performed to test significance. Results. The EV was smaller than expected for GA in fetuses with structural congenital abnormalities (−35% p < 0.001, z -score −1.44 p < 0.001 ), whereas CRL was not (−6.43% p = 0.118, z -score −0.43 p = 0.605 ). Conclusions. CRL is a less reliable parameter to determine growth restriction in fetuses with structural congenital abnormalities as compared with EV. By measuring EV, growth restriction in first-trimester fetuses with structural congenital abnormalities becomes more evident and enables an earlier detection of these cases.